Dramaturgia da improvisação: reflexões de um fazer composicional - Vieira, Mariane Araujo (2021)
This dissertation investigated the dimension of dramaturgy in real-time composition in dance. To this end, the text is divided into two parts. The first one approaches real-time composition focusing on the artistic experiences of the Núcleo de Estudos em Improvisação em Dança (Center for Studies in Dance Improvisation) and on the interviews with Líria Morays, Dudude Hermann, and Diogo Granato. The second part presents important artistic and historical dimensions for the construction of the reflection about dramaturgy and improvisation in the contemporary dance scene, seeking to support the discussion on the concept of Improvisational Dramaturgy, which is the central theme of this work. The text discusses a myriad of topics, such as the artistic practice in improvisation; the particularities of improvisational making; the use of rules as restrictions and tools of a game in real-time composition; the aspects of preparation in improvisation to construct dramaturgy; the idea of autonomy and authorship of creative making in real time; the ephemerality, transience, and uniqueness of creation in improvisational dramaturgy; the elaboration of dramaturgy as part of the work of improvisers and spectators; the performative dimensions of improvisation and the event as an essential element to the understanding of improvisational dramaturgy as a weave of emergencies and affections that take place in the body and in all the materiality of the scene. This work dialogues with the contemporary dance scene and seeks to set the grounds for improvisation as a field of performance and knowledge itself. We hope that this work can open up new horizons and be a reference for future academic or professional works in the field of dance, dramaturgy, and improvisation.